A Comparative Study to Evaluate Myogenic Differentiation Potential of Human Chorion versus Umbilical Cord Blood-derived Mesenchymal Stem Cells. Issue 4 (August 2017) - Bana, Nikoo; Sanooghi, Davood; Soleimani, Mansoureh; Hayati Roodbari, Nasim; Alavi Moghaddam, Sepideh; Joghataei, Mohammad Taghi; Sayahpour, Forough Azam; Faghihi, Faezeh
Highlights: Human Chorion- derived Mesenchymal Stem Cells (C-MSCs) are potent to differentiate into myoblast- like cells after treatment with 5-azacytidine. Human Umbilical Cord Blood- derived Mesenchymal Stem Cells (UCB-MSCs) are potent to differentiate into myoblast- like cells after treatment with 5-azacytidine. A significant upregulation in the expression of some myogenic markers; including Desmin and alpha- MHC was observed in human C-MSCs compared with UCB-MSCs. 5-azacytidine could not induce the expression of GATA-4 in C-MSCs or UCB-MSCs. Abstract: Objective: Musculodegenerative diseases threaten the life of many patients in the world. Since drug administration is not efficient in regeneration of damaged tissues, stem cell therapy is considered as a good strategy to restore the lost cells. Since the efficiency of myogenic differentiation potential of human Chorion- derived Mesenchymal Stem Cells (C-MSCs) has not been addressed so far; we set out to evaluate myogenic differentiation property of these cells in comparison with Umbilical Cord Blood- derived Mesenchymal Stem Cells (UCB-MSCs) in the presence of 5-azacytidine. Materials & methods: To do that, neonate placenta Umbilical Cord Blood were transferred to the lab. After characterization of the isolated cells using flowcytometry and multilineage differentiation capacity, the obtained Mesenchymal Stem Cells were cultured in DMEM/F12 supplemented with 2% FBS and 10 μM of 5-azacytidine to induce myogenic differentiation. Real-time PCR and immunocytochemistry were used to assess the myogenic properties of the cells. Results: Our data showed that C-MSCs and UCB-MSCs were spindle shape in morphology. They were positive for CD90, CD73 and CD44 antigens, and negative for hematopoietic markers. They also differentiated into osteoblast and adipoblast lineages. Real-time PCR results showed that the cells could express MyoD, desmin and α-MHC at the end of the first week (P < 0.05). No significant upregulation was detected in the expression of GATA-4 in both groups. Immunocytochemical staining revealed the expression of Desmin, cTnT and α-MHC. Conclusions: Results showed that these cells are potent to differentiate into myoblast- like cells. An upregulation in the expression of some myogenic markers (desmin, α- MHC) was observed in C-MSCs in comparison with UCB-MSCs.